Functional, structural, and molecular identification of lymphatic outflow from subconjunctival blebs. (July 2020) - Akiyama, Goichi; Saraswathy, Sindhu; Bogarin, Thania; Pan, Xiaojing; Barron, Ernesto; Wong, Tina T.; Kaneko, Mika K.; Kato, Yukinari; Hong, Young; Huang, Alex S.
Abstract: The purpose of this study is to evaluate outflow pathways from subconjunctival blebs and to identify their identity. Post-mortem porcine (n = 20), human (n = 1), and bovine (n = 1) eyes were acquired, and tracers (fluorescein, indocyanine green, or fixable/fluorescent dextrans) were injected into the subconjunctival space to create raised blebs where outflow pathways were visualized qualitatively and quantitatively. Rodents with fluorescent reporter transgenes were imaged for structural comparison. Concurrent optical coherence tomography (OCT) was obtained to study the structural nature of these pathways. Using fixable/fluorescent dextrans, tracers were trapped to the bleb outflow pathway lumen walls for histological visualization and molecular identification using immunofluorescence against lymphatic and blood vessel markers. Bleb outflow pathways could be observed using all tracers in all species. Quantitative analysis showed that the nasal quadrant had more bleb-related outflow pathways compared to the temporal quadrant (nasal: 1.9±0.3 pathways vs. temporal: 0.7±0.2 pathways; p = 0.003). However, not all blebs resulted in an outflow pathway (0-pathways = 18.2%; 1-pathway = 36.4%; 2-pathways = 38.6%; and 3-pathways = 6.8%). Outflow signal was validated as true luminal pathways using optical coherence tomography and histology. Bicuspid valves were identified in the direction of flow in porcine eyes. Immunofluorescence of labeled pathways demonstrated a lymphatic (Prox-1 and podoplanin) but not a blood vessel (CD31) identity. Therefore, subconjunctival bleb outflow occurs in discrete luminal pathways. They are lymphatic as assessed by structural identification of valves and molecular identification of lymphatic markers. Better understanding of lymphatic outflow may lead to improved eye care for glaucoma surgery and ocular drug delivery. Highlights: Glaucoma bleb-forming surgeries rely upon subconjunctival aqueous outflow. Subconjunctival drug delivery is limited by subconjunctival aqueous outflow. Subconjunctival outflow is hypothesized to be via lymphatics or blood vessels. Structural/molecular imaging demonstrates use of the lymphatic route. Better understood, enhancing/minimizing lymphatic outflow may benefit eye care.